2011
DOI: 10.1071/rj11032
|View full text |Cite
|
Sign up to set email alerts
|

Managing for rainfall variability: impacts of grazing strategies on perennial grass dynamics in a dry tropical savanna

Abstract: Rainfall variability remains a major challenge to sustainable grazing management in northern Australia with perennial grasses the key to the stability of the resources that maintain a sustainable grazing industry. This paper describes the dynamics of five perennial grasses – Bothriochloa ewartiana (Domin) C.E. Hubb., Chrysopogon fallax S.T. Blake, Aristida spp., Panicum effusum R. Br. and Heteropogon contortus (L.) P. Beauv. ex Roem. & Schult. in relation to three grazing strategies – moderate stocking at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…Clearly, management objectives for specific tropical pastures systems vary widely; aspects of management of tropical pastures to improve performance of grazing animals have been reviewed by Minson (1990), Humphreys (1991), Poppi et al (1997) and Lemaire et al (2009). In recent years, the management objectives have often focused on improving the vegetation, sustainability, biodiversity and nutrient cycling of the ecosystems (Ash et al, 2011;Orr and O'Reagain, 2011) as essential aspects of sustainable grazing systems. However, historically there has been limited focus on various objectives which relate to the multiple functions of grassland.…”
Section: Strategies For Management Of Grasslandsmentioning
confidence: 99%
“…Clearly, management objectives for specific tropical pastures systems vary widely; aspects of management of tropical pastures to improve performance of grazing animals have been reviewed by Minson (1990), Humphreys (1991), Poppi et al (1997) and Lemaire et al (2009). In recent years, the management objectives have often focused on improving the vegetation, sustainability, biodiversity and nutrient cycling of the ecosystems (Ash et al, 2011;Orr and O'Reagain, 2011) as essential aspects of sustainable grazing systems. However, historically there has been limited focus on various objectives which relate to the multiple functions of grassland.…”
Section: Strategies For Management Of Grasslandsmentioning
confidence: 99%
“…The HSR strategy stocked at about twice LTCC gave good economic and animal performance in the initial wet years but suffered major economic loss in subsequent dry years through high costs, poor individual animal production and reduced product value at the meatworks. The strategy was also unsustainable with stocking rates having to be reduced in dry years and perennial grass density and basal area declining (Orr and O'Reagain, 2011). Profitability recovered in later good rainfall years, but after 13 years the overall profitability of the HSR was by far the lowest of all strategies (Figure 1).…”
Section: Insights From Grazing Trialsmentioning
confidence: 99%
“…Since then, some research has suggested plants, as well as livestock, benefit when paddocks are rested from herbivory (Sampson 1951;Voisin 1959;Davies 1976;Undersander et al 2002;Oates et al 2011;O'Reagain et al 2011;Teague et al 2013). However, other research does not support this (Herbel 1974;Gammon 1978;Van Poollen and Lacey 1979;Fales et al 1995;Hodgson and Illius 1996;Pulido and Leaver 2003;Briske et al 2008;Orr and O'Reagain 2011). The reasons for this disparity are many, some clear cut while others are more controversial (Briske et al 2014;Teague 2014).…”
Section: Stocking Strategiesmentioning
confidence: 90%